What is known about adolescent dysmenorrhoea in (and for) community health settings? - Dixon, Sharon; Hirst, Jennifer; Taghinejadi, Neda; Duddy, Claire; Vincent, Katy; Ziebland, Sue (Frontiers in Reproductive Health, 2024)
Dysmenorrhoea affects many adolescents with significant impacts on education and well-being. In the UK, most of the adolescents who seek care (and many never do), will do so through general practice (primary care). There is little evidence about community experiences or management of adolescent dysmenorrhoea or specific resources to support shared-decision making in general practice, although there are evidence-based treatments to offer. Primary care encounters also represent potential opportunities to consider whether the possibility of underlying or associated health conditions contributing to symptoms of dysmenorrhoea, but there is little epidemiological evidence about prevalence from within community health settings to inform this. This mixed-methods narrative synthesis collates community and specialist evidence, with a community health perspective from 320 papers. We highlight areas of tension or conflicted evidence relevant to primary care alongside areas of uncertainty and research gaps identified through this synthesis with input from lived experience advisers.